The Kedah Domestic Water Supply in the Second Malaya Plan 1960-1965 - Abdullah, Mohd Firdaus; Mohd Noor, Arba'iyah (Melayu: Jurnal Antarabangsa Dunia Melayu, 2020)
This paper highlights the role of the Kedah Government in managing water supply facilities in the Second Malaya Plan from 1960 to 1965. The year 1960 was choosen due to the planning and implementation of water supply projects throughout the state of Kedah, while 1965 was chosen following the end of the Second Malaya Plan which aimed to improve the standard of living of Malaysians. This research used some materials and sources from the National Archives of Malaysia, the National Archives of Kedah/Perlis Branch, Wisma Darul Aman, Kedah Public Library and University Malaya Main Library. The findings of the study show that the Kedah Government successfully developed water supply facilities in the state of Kedah within the stated period, which set the momentum for the implementation of the water supply projects thereafter. Keywords: water supply, domestic, Kedah, development, Second Malaya Plan